Diversifikasi Sumber Keuangan Perguruan Tinggi Melalui Pendirian Koperasi Syariah - Maulida, Minati; Nabil, Muhammad; Sulaeman, Sulaeman; Gunawan, Muhammad Ali (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2024)
The quality of higher education does not only talk about the Tri Dharma of Higher Education, but many other aspects that must be improved, including from the financial side. There needs to be diversification (diversity of financial sources) as an effort to improve the quality of education through other financial sources. One of the solutions that can be done is through the establishment of Sharia Cooperatives. This study aims to determine the effectiveness of diversifying financial resources of higher education through sharia cooperatives. The object of this research is STAI Ki Ageng Pekalongan. This research is descriptive research with a qualitative approach. The data collection techniques carried out are observation (observation), interviews, and documentation. The results of this research analysis conclude that through the establishment of sharia cooperatives in STAI Ki Ageng Pekalongan can help in diversifying financial resources. The presence of sharia cooperatives can reduce dependence on only one source of income and can be used to improve the quality of education at STAI Ki Ageng Pekalongan.